Technological Aspects and Evaluation Methods for Polymer Matrices as Dental Drug Carriers - Dorota Kida; Tomasz Konopka; Kamil Jurczyszyn; Bożena Karolewicz (Biomedicines, 2023)
The development of polymer matrices as dental drug carriers takes into account the following technological aspects of the developed formulations: the composition and the technology used to manufacture them, which affect the properties of the carriers, as well as the testing methods for assessing their behavior at application sites. The first part of this paper characterizes the methods for fabricating dental drug carriers, i.e., the solvent-casting method (SCM), lyophilization method (LM), electrospinning (ES) and 3D printing (3DP), describing the selection of technological parameters and pointing out both the advantages of using the mentioned methods and their limitations. The second part of this paper describes testing methods to study the formulation properties, including their physical and chemical, pharmaceutical, biological and in vivo evaluation. Comprehensive in vitro evaluation of carrier properties permits optimization of formulation parameters to achieve prolonged retention time in the dynamic oral environment and is essential for explaining carrier behavior during clinical evaluation, consequently enabling the selection of the optimal formulation for oral application.